Adaptation of macroalgal indexes to evaluate the ecological quality of coastal waters in oceanic islands with subtropical influence: the Azores (Portugal) - Gabriel,Daniela (2014)
Due to their sedentary characteristic and the sensibility of certain taxa to excessive nutrients or toxic substances, the benthic macroalgal assemblage of a given locality reflects the effects of long-term exposure to pollution. For this reason, seaweeds have been used to assess the environmental condition of coastal communities. Since the Water Framework Directive from the European Union (WFD/EU) was launched, several ecological indexes have been developed for ecological quality assessment and monitoring. Those indexes are based on different features that can be easily observed and combined into a single value, which in turn is translated to stakeholders as an ecological status.